2015
DOI: 10.1007/978-3-319-18988-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Procedures and Collaborative Information Seeking: A Study of Emergency Departments

Abstract: Abstract. Information seeking is a central and inherently collaborative activity in the emergency department (ED), which is the common entry point to hospitals for nearly all acute patients. In this paper, we investigate how ED clinicians' collaborative information seeking (CIS) is shaped by the procedures that they follow in the ED. Based on observations in two Danish EDs, we identify four procedures prominent to how CIS is accomplished: the triage procedure, the timeouts, the coordinating nurse, and the recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…To spell out how a procedure facilitates situated action each information-seeking instance may be viewed as a specific configuration of components -such as information need, people, completion criteria, location, and time -that have to be properly integrated to succeed. Hertzum and Reddy (2015) argue that procedures facilitate information seeking by pre-specifying some of these components. Thereby, fewer components require ad hoc specification.…”
Section: Workplace Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…To spell out how a procedure facilitates situated action each information-seeking instance may be viewed as a specific configuration of components -such as information need, people, completion criteria, location, and time -that have to be properly integrated to succeed. Hertzum and Reddy (2015) argue that procedures facilitate information seeking by pre-specifying some of these components. Thereby, fewer components require ad hoc specification.…”
Section: Workplace Proceduresmentioning
confidence: 99%
“…Relatedly, the timeout procedure specifies where and when the physicians meet to walk through the patients but for example leaves unspecified what information to look for, what criteria to apply in interpreting it, and how to divide the limited duration of the timeout among the patients. By pre-specifying (Hertzum & Reddy, 2015) some of the components in triage and timeouts the procedures structure and simplify the clinicians' performance of these tasks. But the clinicians' professional knowledge and experience remain critical to their competent application of the procedures.…”
Section: Novicesmentioning
confidence: 99%
“…Although previous research in public sector organizations has reported the use of various arrangements for information intermediation in employees daily work (cf. Frederiksen and Hansen, 2022;Hertzum and Reddy, 2015;K€ ans€ akoski, 2017), our identification of the intertwined role of fixed and flexible gatekeeping structures that support public service delivery is a novel contribution to the fields of information management and public administration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being an information display, the whiteboard also creates a physical place where actors meet [13]. They may visit the area around the whiteboard to interact with the whiteboard or to consult a colleague, who is there to interact with the whiteboard, consult a colleague or make herself available for consultation [14]. While the three strengths are described on the basis of studies of electronic whiteboards, it appears likely that the same strengths exist for wall-size displays, tabletop interfaces, and other large, shared displays.…”
Section: Overview and Large Shared Displaysmentioning
confidence: 99%